2021
DOI: 10.1093/jhered/esab009
|View full text |Cite
|
Sign up to set email alerts
|

Limited Evidence for Parallel Evolution Among Desert-AdaptedPeromyscusDeer Mice

Abstract: Warming climate and increasing desertification urges the identification of genes involved in heat- and dehydration-tolerance to better inform and target biodiversity conservation efforts. Comparisons among extant desert adapted species can highlight parallel or convergent patterns of genome evolution through the identification of shared signatures of selection. We generate chromosome-level genome assembly for the canyon mouse (Peromyscus crinitus) and test for signature of parallel evolution by comparing signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 140 publications
(188 reference statements)
0
19
0
Order By: Relevance
“…Although rodents of the genus Peromyscus look similar to Mus mice in appearance and have similar genome sizes, they last shared a common ancestor with Mus ~25 million years ago (Steppan et al 2004) and have very karyotypically stable genomes (2n=48; Smalec et al 2019), even more so than great apes. As a rodent lineage with increasing genomic resources (Colella et al 2020;Tigano et al 2020;Colella et al 2021) and conserved genome structure, Peromyscus offers similarities and contrasts to both the Mus and the great apes lineages, thus representing an ideal third clade to understanding the role of genome structure stability and the relationships between chromosome size, recombination, diversity, and divergence in mammals. For example, similar to the great apes (Hellman et al 2003) but contrasting with M. musculus, the cactus mouse (Peromyscus eremicus) shows a strong inverse correlation between chromosome size and π (Tigano et al 2020); conserved synteny, recombination rates, and crossover patterning among Peromyscus species (Peterson et al 2019;Smalec et al 2019) together suggest that this relationship between chromosome size and π may be common among species in this genus.…”
Section: Introductionmentioning
confidence: 99%
“…Although rodents of the genus Peromyscus look similar to Mus mice in appearance and have similar genome sizes, they last shared a common ancestor with Mus ~25 million years ago (Steppan et al 2004) and have very karyotypically stable genomes (2n=48; Smalec et al 2019), even more so than great apes. As a rodent lineage with increasing genomic resources (Colella et al 2020;Tigano et al 2020;Colella et al 2021) and conserved genome structure, Peromyscus offers similarities and contrasts to both the Mus and the great apes lineages, thus representing an ideal third clade to understanding the role of genome structure stability and the relationships between chromosome size, recombination, diversity, and divergence in mammals. For example, similar to the great apes (Hellman et al 2003) but contrasting with M. musculus, the cactus mouse (Peromyscus eremicus) shows a strong inverse correlation between chromosome size and π (Tigano et al 2020); conserved synteny, recombination rates, and crossover patterning among Peromyscus species (Peterson et al 2019;Smalec et al 2019) together suggest that this relationship between chromosome size and π may be common among species in this genus.…”
Section: Introductionmentioning
confidence: 99%
“…Similar methods on hot-desert fat-tail sheep breeds and goats (Capra hircus) identified many candidate regions spanning genes and/or pathways significantly enriched for fat metabolism, insulin signaling, kidney function, oxidative stress and DNA repair, response to heat and UV radiation, body size development, and melanogenesis [17,20]. Species of the genus Peromyscus have also been used in case studies in population genomics as examples of rapid environmental/ecological differentiation [18,21]. Different arid-dwelling species repeatedly evolved during the radiation of the genus in North America.…”
Section: Population-specific Desert Adaptationmentioning
confidence: 99%
“…Several studies of different desert mammals have identified genes, and functional classes of genes and pathways, involved in fat metabolism [17,21,32,39,55], thyroid-induced metabolism [12], salt metabolism and prevention of high blood pressure [13,16,34], insulin signaling Box 1. Endurer-Evader-Evaporator Concept Aiming to summarize and categorize decades of classic literature on desert adaptations in species occupying distinct ecological niches, Willmer et al [2] proposed a classification system relative to extreme temperatures and body size.…”
Section: Convergent Evolution At the Genetic Levelmentioning
confidence: 99%
See 2 more Smart Citations